2015
DOI: 10.1007/s00405-015-3718-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Arabic version of the “Sniffin’ Sticks” odor identification test

Abstract: 2b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…At last 24 articles were included (see selection flowchart in Figure 1). The studies (16,19,20,28,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) included for each of the three groups are shown in Table 1. Table 1 showed the demographic characteristics of participants and measures used in odor identification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At last 24 articles were included (see selection flowchart in Figure 1). The studies (16,19,20,28,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) included for each of the three groups are shown in Table 1. Table 1 showed the demographic characteristics of participants and measures used in odor identification.…”
Section: Resultsmentioning
confidence: 99%
“…We also conducted a subdivision comparison between female and male in the age 16-35 (16,19,20,40,45,47,49,52) . However, compared to the age 18-50, the effect size was relatively small (Cohen's d=0.36, 95% CI: 0.18 to 0.54), though a significant difference (Z = 3.87, p=0.0001) was found that female outperformed male in odor identification.…”
Section: Demographic Characteristics and Measures Used In Odor Identimentioning
confidence: 99%
“…Threshold. The odor threshold subtest contains 16 triplets (numbered [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], in which only one of the triplets contains nbutanol and solvent and the other two contain only the solvent. The subjects were asked to identify the pen with n-butanol in different concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the I tests has been examined both in terms of internal validity 10,[12][13][14] and external validity [13][14][15][16][17][18] in other languages and cultures. Different cultural components have major impact on the exposure and frequency of foods and odors, and consequently on our familiarity with odors.…”
Section: Introductionmentioning
confidence: 99%
“…Several diagnostic tools have been developed to assess human sensitivity to odors and to diagnose olfactory dysfunctions (Doty, Avron, Lee, Marcus, & William Lee, ; Hummel, Sekinger, Wolf, Pauli, & Kobal, ). Attempts have been made to advance these methods by extension (Sorokowska, Albrecht, Haehner, & Hummel, ), reduction (Hummel, Pfetzing, & Lötsch, ), or cultural adaptation (Catana, Negoiaș, Maniu, Porojan, & Cosgarea, ; Konstantinidis et al, ; Oleszkiewicz et al, ; Silveira‐Moriyama et al, ; Sorokowska & Hummel, ) to provide most accurate diagnosis of olfactory function. Recently, chemical properties of odors utilized in the Sniffin’ Sticks test battery gained scientific attention and prompted efforts to test the hypothesis stating that more complex stimuli, that is, mixtures of odorants are more efficient in activating ORs and thus less sensitive to individual variability in ORs phenotype.…”
Section: Introductionmentioning
confidence: 99%